The Effect of Annealing on The Structural and Optical Properties of SnS Thin Films - D.A. Mfarej, Hind; R. M.Al-Sarraf, Abdul Hameed; Al Anssari, Ramiz A. Mohammd; F. Habubi, Nadir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films of pure tin mono-sulfide SnS with thicknesses of (0.85) Î¼m were prepared by chemical spray pyrolysis technique and annealed for two hours with 673K.The effect of annealing on structural and optical properties for films prepared was studied. X-Ray diffraction analysis showed the polycrystalline with orthorhombic structure. It was found that annealing process increased the intensity of diffraction peaks. Optical properties of all samples were studied by recording the absorption and transmission spectrum in the range of wave lengths (300-900) nm. The optical energy gap for direct forbidden transition and indirect allowed transition were evaluated